Sīratunnabī : yaʻnī, savāniḥ aqdas ḥaz̤rat sarvar-i ʻālam Muḥammad rasūl Allāh ṣallá Allāh ʻalayhi va-sallam - Shibli Numani, Muhammad, 1857-1914 (SAMP early 20th-century Indian books project ;, 1918)
Biography of Prophet Muḥammad, d. 632.